Brachytherapy in the treatment of lung cancer – a valuable solution - Skowronek, Janusz (Journal of Contemporary Brachytherapy, 2015)
The majority of patients with lung cancer are diagnosed with clinically advanced disease. Many of these patients have a short life expectancy and are treated with palliative aim. Because of uncontrolled local or recurrent disease, patients may have significant symptoms such as: cough, dyspnea, hemoptysis, obstructive pneumonia, or atelectasis. Brachytherapy is one of the most efficient methods in overcoming difficulties in breathing that is caused by endobronchial obstruction in palliative treatment of bronchus cancer. Efforts to relieve this obstructive process are worthwhile, because patients may experience improved quality of their life (QoL). Brachytherapy plays a limited but specific role in definitive treatment with curative intent in selected cases of early endobronchial disease as well as in the postoperative treatment of small residual peribronchial disease. Depending on the location of the lesion, in some cases brachytherapy is a treatment of choice. This option is fast, inexpensive, and easy to perform on an outpatient basis. Clinical indications, different techniques, results, and complications are presented in this work.